Improving Organisational Learning in Project-Based Organisations Through the Translation of Project Lessons Learnt into Project Risks - Bredell, C.; Tshuma, B. (South African Journal of Industrial Engineering, 2025)
This study examines the translation of lessons learnt into risks in project-based organisations to improve organisational learning through the development of a knowledge transfer model. A qualitative analysis of semi-structured interviews , a focus group interview, and an organisational repository review in a single case study organisation revealed that framing lessons as risks enhances organisational learning by strengthening critical practices such as systematic problem-solving, learning from past experiences, and efficient knowledge transfer. The proposed model configures the application of risk-phrased lessons learnt to promote the transfer of knowledge and to foster organisational learning in project-based organisations.